1983
DOI: 10.1002/jor.1100010410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cement pressure and bone strength on polymethylmethacrylate fixation

Abstract: The effect of the quality of the bone and of the cement pressurization magnitude and duration on the fixation achieved with polymethylmethacrylate (PMMA) bone cement is studied in vitro. Seventy-one cement-bone interface specimens, prepared under various conditions of pressurization of low-viscosity bone cement, are tested in tension. The load at failure and the maximum cement penetration are measured to assess the fixation achieved, and the quality of the bone is assessed by determining the compressive streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
80
0
13

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 7 publications
4
80
0
13
Order By: Relevance
“…However, injection of viscous cement with low pressure decreases the penetration of the cement into the microstructure of cancellous bone [4]. Krause et al [16] reported that doughy cement on an unclean surface resulted in a very low interface strength compared to a low-viscosity cement made to penetrate a cleaned bone surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, injection of viscous cement with low pressure decreases the penetration of the cement into the microstructure of cancellous bone [4]. Krause et al [16] reported that doughy cement on an unclean surface resulted in a very low interface strength compared to a low-viscosity cement made to penetrate a cleaned bone surface.…”
Section: Discussionmentioning
confidence: 99%
“…Three independent variables, which are under the control of the surgeon, determine the intrusion characteristics of the cement: magnitude of cement pressure, duration of pressure application, and viscosity of acrylic cement (Askew et al 1984). Achievement of an adequate cement pressure and penetration in the acetabulum is particularly difficult, given its appearance and anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of fixation of the bone-cement interface depends on the quality of the bone bed, the intrinsic properties of the bone cement, and the depth of penetration of the cement. Increased penetration into the porous bone has been shown experimentally to lead to a stronger interface (Askew et al 1984, Maltry et al 1995.…”
mentioning
confidence: 98%
“…The aspirator retractor, designed in 2000 and used in our series, reportedly improved cement penetration into trabecular bone in one study [17]. Cement penetration greater than 2 mm and an ideal penetration of 3 to 5 mm reportedly produces the strongest cement-bone interface [1,18,20]. However, we could not confirm an improvement in cement intrusion in this series.…”
Section: Discussionmentioning
confidence: 57%